Penentuan Kadar Enzim Kolinesterase pada Petani Pengguna Pestisida Organofosfat Berdasarkan Frekuensi Penyemprotan - Yoga Saputra, Devi; Purwati; Harningsih, Tri (Jurnal Farmasi (Journal of Pharmacy), 2020)
Pesticides are generally interpreted as toxic chemicals that are used to control pests that harm humans. Pesticides have been used to increase agricultural production, plantations and eradicate disease vectors. The frequency of spraying and the high volume of pesticides used indicates the decisive role of these pesticides in crop production, these pesticides cannot be released from agricultural planting. Most farmers spray themselves and have their own sprayers so that they have the flexibility to spray. Vegetable growers have a high risk of pesticide poisoning. This research uses the literature study method. Data collection uses secondary data taken from scientific journals and scientific papers with the last 10 years vulnerable. Data analysis uses descriptive analysis. Cholinesterase enzyme is an enzyme found in celluloid fluid. It used to stop the action of acetylcholine by hydrolyzing into colin and acetic acid. Acetylcholine is an introductory nerve located in the entire central nervous system, autonomic nerve (sympathetic and parasymatic) and the somatic nervous system. The results of the study stated that 4 journals stated that there was a correlation between the frequency of spraying on the enzyme level cholinesterase, while 2 journals stated that there was no relationship. The frequency of spraying affects the decrease in the level of theenzyme cholinesterase in organophosphate pesticide farmers.